ESTUDO QUIMIOTAXONÔMICO DE LIQUENS DO GÊNERO STEREOCAULON E BUSCA DE COMPOSTOS BIOATIVOS - Aline Siqueira Gianini (2022)
Lichens produce many compounds and those of the polyketide pathway stand out; are phenolic compounds, most of which are exclusive to these organisms, in addition to long-chain fatty acids. These compounds play an important role in the chemotaxonomy of lichens, as they serve as chemical markers for identification at different taxonomic levels. In this work, 151 exsiccates of lichens of the genus Stereocaulon collected in Brazil, Antarctica, Chile and Argentina were analyzed using thin layer-chromatography, high performance liquid chromatography coupled with mass spectrometer, microcrystallization and Nuclear Magnetic Resonance of 1H and 13C. 24 compounds were identified: rangiformic, pseudonorrangiormic, vinapraesorediosic B and bourgeanic acids (fatty acids); lobaric, norstictic, menegazziaic, hypoconstictic, colensoic, stictic acids (depsidones); atranorin, gyrophoric acid, anziaic acid, stenosporic acid, 2-O-methylnorstenosporic acid and perlatolic acid (depsides); strepsilin (dibenzofuran); lobarin (diphenylether), oxysiphulin (chromone) and five new compounds: the depside 1 ´´-oxo -ene''-ene''' perlatolic acid or -ene''-ene''' glomelliferic acid or -ene''-ene''' miriquidic acids and the depsidones: 2''-ene lobaric, 3''-ene lobaric and 4''-ene lobaric and -ene´´´ lobaric acids. The chemical composition together with the morphological analysis of each specimen allowed to identify the species: Stereocaulon corticatulum, Stereocaulon alpinum (3 chemical groups), Stereocaulon melanopotamicum (2 chemical groups), Stereocaulon implexum, Stereocaulon tomentosum (4 chemical groups), Stereocaulon tomentosum var. capitatum (2 chemical groups), Stereocaulon ramulosum and Stereocaulon argus. Extracts of the species S. corticatulum, S. alpinum, S. tomentosum and S. ramulosum were evaluated for antibacterial activity against Staphylococcus aureus (clinical and standard strain), Enterococcus faecium (clinical strain) and Escherichia coli (standard strain), and antioxidant against the free radical DPPH (1,1-diphenyl-2-picrylhydrazyl). The extract of S. ramulosum was the most active, with MIC of 31.25 μg/mL against the two strains of S. aureus; bioautography showed that all substances present in the extract were responsible for the activity. The extracts of the other species showed MIC  125 μg/mL. The evaluation of the antioxidant activity of the extracts indicated more than ten active substances. Our results represent a contribution to the detailed knowledge of the chemical composition of 09 species of lichens of the genus Stereocaulon.